Analysis of feline and canine allergen components in patients sensitized to pets. Issue 1 (December 2016) - Ukleja-Sokołowska, Natalia; Gawrońska-Ukleja, Ewa; Żbikowska-Gotz, Magdalena; Socha, Ewa; Lis, Kinga; Sokołowski, Łukasz; Kuźmiński, Andrzej; Bartuzi, Zbigniew
Abstract Background Component resolved allergen diagnosis allows for a precise evaluation of the sensitization profiles of patients sensitized to felines and canines. An accurate interpretation of these results allows better insight into the evolution of a given patients sensitizations, and allows for a more precise evaluation of their prognoses. Methods 70 patients (42 women and 28 men, aged 18–65, with the average of 35.5) with a positive feline or canine allergy diagnosis were included in the research group. 30 patients with a negative allergy diagnosis were included in the control group. The total IgE levels of all patients with allergies as well as their allergen-specific IgE to feline and canine allergens were measured. Specific IgE levels to canine (Can f 1, Can f 2, Can f 3, Can f 5) and feline (Fel d 1, Fel d 2, Fel d 4) allergen components were also measured with the use of the ImmunoCap method. Results Monosensitization for only one canine or feline component was found in 30% of patients. As predicted, the main feline allergen was Fel d 1, which sensitized as many as 93.9% of patients sensitized to felines. Among 65 patients sensitized to at least one feline component, for 30 patients (46.2%) the only sensitizing feline component was Fel d 1. Only 19 patients in that group (63.3%) were not simultaneously sensitized to dogs and 11 (36.7%), the isolated sensitization to feline Fel d 1 notwithstanding, displayed concurrent sensitizations to one of the canine allergen components. Fel d 4 sensitized 49.2% of the research group.64.3% of patients sensitized to canine components had heightened levels of specific IgE to Can f 1. Monosensitization in that group occurred for 32.1% of the patients. Sensitization to Can f 5 was observed among 52.4% of the patients. Conclusions Concurrent sensitizations to a few allergic components, not only cross-reactive but also originating in different protein families, are a significant problem for patients sensitized to animals.